Can the attention training technique reduce burnout in junior elite athletes? - Moen, F.; Wells, A. (International Journal of Coaching Science, 2016)
The primary purpose of the present study was to investigate the effects of the attention training technique on junior elite athletes` level of burnout. We also examine an ancillary question of whether the technique impact on mindfulness. The results showed that there was a significant decrease in in burnout amongst the ATT group but not the control group. In the ATT group, but not the control, mindfulness increased. The results are discussed based on the changes in the athletes` attentional awareness and control.